2005
DOI: 10.1523/jneurosci.1711-05.2005
|View full text |Cite
|
Sign up to set email alerts
|

Parsing Molecular and Behavioral Effects of Cocaine in Mitogen- and Stress-Activated Protein Kinase-1-Deficient Mice

Abstract: , demonstrating the existence of drug-induced chromatin remodeling in vivo. In MSK1 knock-out (KO) mice CREB and H3 phosphorylation in response to cocaine (10 mg/kg) were blocked, and induction of c-Fos and dynorphin was prevented, whereas the induction of Egr-1 (early growth response-1)/zif268/Krox24 was unaltered. MSK1-KO mice had no obvious neurological defect but displayed a contrasted behavioral phenotype in response to cocaine. Acute effects of cocaine and dopamine D 1 or D 2 agonists were unaltered. Sen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

16
284
4
1

Year Published

2007
2007
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 269 publications
(305 citation statements)
references
References 50 publications
16
284
4
1
Order By: Relevance
“…DARPP-32 also regulates nuclear events, as demonstrated by alterations of drug-induced gene expression in mice lacking DARPP-32 or bearing a point mutation of Thr-34 12,13 . Part of the control exerted by DARPP-32 on transcription is mediated by activation of the ERK pathway, dependent on the concomitant stimulation of D1R and glutamate NMDA receptors 13,14 . However, the precise mechanisms of information transfer from the cytoplasm to the nucleus of striatal neurons are still poorly characterized.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…DARPP-32 also regulates nuclear events, as demonstrated by alterations of drug-induced gene expression in mice lacking DARPP-32 or bearing a point mutation of Thr-34 12,13 . Part of the control exerted by DARPP-32 on transcription is mediated by activation of the ERK pathway, dependent on the concomitant stimulation of D1R and glutamate NMDA receptors 13,14 . However, the precise mechanisms of information transfer from the cytoplasm to the nucleus of striatal neurons are still poorly characterized.…”
Section: Discussionmentioning
confidence: 99%
“…The phosphorylation of H3 on Ser-10 is a key step in nucleosomal response 28,32 and is crucial for memory formation 33 . It is increased in the striatum after cocaine administration in vivo, and this response is functionally important 14,34 . Cocaine induced an intense phosphoSer-10-H3 signal in the nuclei of a number of striatal neurons in wild type mice, whereas this effect was absent in either T34A-DARPP-32 or S97A-DARPP-32 mice (Fig.5a).…”
Section: Nuclear Translocation Of Darpp-32 Is Essential For D1r-regulmentioning
confidence: 98%
“…Several studies suggest that dynamic histone acetylation and deacetylation processes are also active in postmitotic neurons [12,20,21,27]. Recently, it has been shown that both acute and chronic cocaine administration are able to induce specific histone modification at different gene promoters in the striatum [6,20,22]. Furthermore, treatment with HDAC inhibitors alter locomotor and rewarding responses to cocaine [20].…”
Section: Introductionmentioning
confidence: 99%
“…For example, Aurora kinases A and B have been demonstrated to catalyze the addition of phosphate groups at H3S10, whereas mitogen-activated protein (MAP) kinase phosphatase-1 has previously been shown to promote the enzymatic removal of phosphate groups at this residue (Pascreau et al, 2003;Kinney et al, 2009). In brain, the dopamine and cAMP regulated protein phosphatase inhibitor, DARPP-32, as well as the MAP kinase, MSK1, provide excellent examples of enzymes regulating H3S10p in response to environmental stimuli, indicating histone phosphorylation as an important regulator of adult neuronal function (Brami-Cherrier et al, 2005;Stipanovich et al, 2008).…”
Section: Histone Phosphorylation and Cross Talk Interactions In The Cnsmentioning
confidence: 99%